The role of stakeholders in development of social economy organizations in Poland: An integrative approach - Norbert Laurisz (Administrative Sciences, 2019)
The aim of this article is to explore key changes in the mode of operation of Polish social economy organizations (SEOs) that result from a social policy targeted at strengthening their independence and sustainability. The activities of SEOs are largely supported by public institutions, but their opportunities for assistance of capacity building are considered insufficient. Owing to the current policy, not only an economic independence, but also the structure and behavior of supported social organizations, especially in their relations with other stakeholders, can be strengthened. Based on the exploratory analysis on how SOEs change their independence and sustainability as a result of implementation of the public policy, a conceptual model of value co-creation will be used. The model enables analyzing the scope and scale of stakeholder engagement in the development of SEOs. The empirical research was conducted using a survey among 112 Polish social economy organizations. The results of the study show that the market-oriented approach not only reduces the scale of relations between SEOs and their stakeholders but also affects the way SEOs work, transforming them to be more like traditional businesses.
Keywords: 350; co-creation; stakeholders; social enterprise; NGO; social economy organization; commercialization; public policy